Mercury and mercury electrodes: The ultimate battle for the naked existence (a consideration) - Navrátil, Tomáš; Švancara, Ivan; Mrázová, Karolina; Nováková, Kateřina; Šestáková, Ivana; Heyrovský, Michael; Pelclová, Daniela (Univerzita Pardubice, 2011)
In this article, the current status and position of mercury as one of the most typical representative of present day's fear from "harmful chemistry" is for the first time concisely reviewed (with 100 refs.). Mercury as such means a danger for the environment and the human beings, but the contemporary life of the civilized man without utilization of this metal element would be hardly imaginable. It is shown that mercury has occupied a significant position in the industry (in mining, as an inevitable component of electrolyzers, batteries, and various lightning devices), in medicine (as amalgams in dentistry or some special medicaments), as well as in physical and chemical laboratories (thermometer and barometers, or as traditional electrodes for polarography and voltammetry). Such a usage of mercury is considered in relation with toxicological aspects, from almost harmless liquid mercury, via potentially harmful Hg2 II- and HgIIprecipitates, up to highly poisonous Hg-vapors or deadly toxic organomercury compounds. The individual forms and compounds are characterized, also using less known or even extreme examples from the past, recent time, as well as from the present, including rather curious reflections of the so-called mercurophobia. Regarding the evaluation of the actual toxicity, numerous inquiries concerning exposures to mercury have been extracted from the Czech Toxicological Information Center (CTIC), gathering the respective data over the period of 1995-2011. Finally, some future prospects mainly, in context with nowadays hugely popularized "green chemistry" are given and possible consequences outlined.
Keywords: mercury; elemental form; mercury compounds; industrial use; toxicological profile; electrochemistry electrodes; present; future; mercury electrodes; laboratory use; review